Intersubjectivity : a cosmology theodicy and narratology of Ubuntu in conversation with the philosophy of organism of A.N. Whitehead - Veldsman, Daniel Petrus (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.